(untitled) - Halvorson, Heidi Halvorson (Boston, Mass., 2018)
Take your cues from the short, powerful 9 Things Successful People Do Differently, where the strategies and goals of the world’s most successful people are on display—backed by research that shows exactly what has the biggest impact on performance. Here’s a hint: accomplished people reach their goals because of what they do, not just who they are.
Keywords: Mục tiêu (tâm lý học),Goal (psychology)